2013
DOI: 10.1097/moo.0b013e32835fb399
|View full text |Cite
|
Sign up to set email alerts
|

The role of allergy in pediatric rhinosinusitis

Abstract: Allergic rhinitis is frequently associated with CRS. The management of CRS should include evaluation of the pediatric patient for allergic disease and the management should be targeted at decreasing the inflammatory response, which will most likely result in better control of the CRS patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…In fact, nasal blockage may occur in AR children, due to edematous mucosa, neurogenic and vascular responses, over-production of secretions, and impaired mucociliary clearance leading to congestion of the ostia and symptoms simulating rhinosinusitis. On the other hand, the blockage leads to stagnant debris and acidotic environment that might stimulate bacteria overgrowth [ 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, nasal blockage may occur in AR children, due to edematous mucosa, neurogenic and vascular responses, over-production of secretions, and impaired mucociliary clearance leading to congestion of the ostia and symptoms simulating rhinosinusitis. On the other hand, the blockage leads to stagnant debris and acidotic environment that might stimulate bacteria overgrowth [ 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…In fact, nasal blockage may occur in AR children, due to edematous mucosa, neurogenic and vascular responses, overproduction of secretions, and impaired mucociliary clearance leading to congestion of the ostia and symptoms simulating rhinosinusitis. On the other hand, the blockage leads to stagnant debris and acidotic environment that might stimulate bacteria overgrowth [34,35]. Histopathological analysis [36,37] demonstrated that pediatric CRS is quite different from the adult form, showing greater inflammatory cellularity, higher density of submucosal lymphocytes, less eosinophilic inflammation, basement membrane thickening, and mucous gland hyperplasia, suggesting a different pathway compared with the adult CRS pattern, which is predominantly characterized by a Th2-oriented response with polypoid changes.…”
Section: Allergy and Chronic Rhinosinusitis (Crs) In Childrenmentioning
confidence: 99%
“…Another study reported that atopic asthmatics suffer from more frequent lower-respiratory-tract infections and have more severe and persistent lower-respiratory-tract symptoms than normal subjects [ 18 ]. Thus, a relevant link between RI and AR exists as underlined by several studies [ 19 20 21 22 23 24 25 26 ]…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the pediatric form is characterized by greater cellularity of chronic inflammatory cell infiltrate, whereas the adult form is characterized by both polypoid changes with edema of the lamina propria and glandular hyperplasia. The population of eosinophils and the proportion of complete epithelial denudation are also different, with a significantly greater extent found in the adult CRS specimens (16). Such differences have led researches to distinguish studies on the role of allergy on CRS between adults and children and to conclude that in adults, the evidence favoring a role for AR in the etiology of the typical case of CRS is weak, whereas in children, causal relationship between allergens and CRS is probably nonexistent (7).…”
Section: Mechanistic Evidencementioning
confidence: 99%
“…And even some specific gene polymorphisms present in CRS have also been found in asthma (14). Several reviews on the role of allergy in CRS, in both adults (11,15) and children (16), can be found in the recent English literature, where epidemiological and experimental studies are mentioned. However, a logical structure for investigating and defining causality in epidemiological studies, such as Bradford-Hill criteria for causation, has not been applied so far.…”
mentioning
confidence: 99%